Opportunities and Challenges for Designing Interactive Applications for Coffee Producers in the Countryside of Brazil - Memento, Gabriela Silva; Santos, Estevão Augusto da Fonseca; Marques, Diego de Souza; Presotto, Pedro Henrique Falleiros Sampaio; Salgado, André de Lima; Freire, André Pimenta (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Brazil is one of the largest coffee producers in the world, with a significant part of its agricultural areas devoted to this crop. People in rural areas in Brazil have several particularities that impact on how they interact with systems to support their daily work, including internet connectivity, mobility and cultural factors including varying educational and digital literacy levels. Despite growing efforts into researching interaction design in rural areas around the world, there is little knowledge about the opportunities and challenges in the context of coffee production in Brazil. This paper presents emerging results from an exploratory qualitative study with eight coffee producers from the south of Minas Gerais in Brazil. The study investigated their current practices in their agricultural endeavours and the technologies used in their work. The results encountered provide insights into opportunities and challenges for designing interactive applications to cater for specific needs of producers in rural areas. The results reflect on themes such as analogic solutions employed in the field, different levels of connectivity, varying levels of digital literacy and acceptance of technologies, agricultural machinery, mobility issues, daily activities performed in the field and sustainability aspects perceived by producers. The findings from these results provide ample discussions for research avenues into the particular context of coffee producers in Brazil in dialogue with recent findings from studies into the rural context worldwide.